2022
DOI: 10.1111/ppe.12878
|View full text |Cite
|
Sign up to set email alerts
|

Early factors associated with risk of developmental coordination disorder in very preterm children: A prospective area‐based cohort study in Italy

Abstract: Background Developmental coordination disorder (DCD) is a motor disorder of unknown aetiology that may have long‐term consequences on daily activities, and psychological and physical health. Studies investigating risk factors for DCD have so far provided inconsistent results. Objectives To assess, using a parent‐report screening tool, risk of DCD in school‐age very preterm children born in Italy, and investigate the associated early biomedical and sociodemographic factors. Methods A prospective area‐based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…This recruitment bias was related to the local organization of care with dedicated referral centres for developmental motor problems (our team), intellectual disability, and speech/language disorders. Despite these possible recruitment biases, the general characteristics of our patients were consistent with those of previous series 25 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This recruitment bias was related to the local organization of care with dedicated referral centres for developmental motor problems (our team), intellectual disability, and speech/language disorders. Despite these possible recruitment biases, the general characteristics of our patients were consistent with those of previous series 25 …”
Section: Discussionsupporting
confidence: 85%
“…Despite these possible recruitment biases, the general characteristics of our patients were consistent with those of previous series. 25 T A B L E 3 Contributing components, main variables contributing for each cluster, and motor and visuospatial subtest results in each cluster. The typical cognitive profile was characterized by a discrepancy between the Verbal Comprehension Index (strong point) and Processing Speed Index (weak point).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Italy also found that SGA was a risk factor for non-CP MD. 57 As SGA is not a risk factor for severe brain lesions, 58 this may explain the absence of association with CP. Low Apgar score, which can reflect poor adaptation at birth was reported to increase the risk of CP in the systematic review from van Lieshout et al 44,59 In their systematic review, Linsell et al 11 concluded that there was some evidence in VPT/very low birth weight populations that the use of postnatal corticosteroids increased the risk of CP, while the use of antenatal corticosteroids reduced risks.…”
Section: Perinatal and Neonatal Risk Factorsmentioning
confidence: 99%
“…In this special issue, the risks associated with social factors and the environment in relation to the outcomes of very preterm survivors are highlighted. Joseph et al 2 demonstrated that social disadvantage is a strong and independent risk factor for lower IQ in extremely preterm adolescents, more so than gestational age at birth, while Zoia et al 8 found parental education and occupation were independently associated with motor functioning and risk for Developmental Coordination Disorder in children born very preterm alongside clinical indicators such as male sex, small for gestational age and retinopathy of prematurity. When considering factors associated with long‐term outcomes, exposure to perinatal interventions should also be considered.…”
mentioning
confidence: 99%